Species loss due to nutrient addition increases with spatial scale in global grasslands - Seabloom, Eric W.; Batzer, Evan; Chase, Jonathan M.; Stanley Harpole, W.; Adler, Peter B.; Bagchi, Sumanta; Bakker, Jonathan; Barrio, Isabel C.; Biederman, Lori; Boughton, Elizabeth H.; Bugalho, Miguel N.; Caldeira, Maria C.; et al. (Ecology Letters)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness (S) as a power function of the sample area (A): S = cAz, where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m2) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co-occur locally, indicated by the SAR intercepts (log c), but did not affect the SAR slopes (z). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales. Fil: Seabloom, Eric W. University of Minnesota; Estados Unidos Fil: Batzer, Evan. University of California at Davis; Estados Unidos Fil: Chase, Jonathan M. German Centre For Integrative Biodiversity Research; Alemania Fil: Stanley Harpole, W. German Centre For Integrative Biodiversity Research; Alemania. Martin-universität Halle-wittenberg; Alemania. Helmholtz Zentrum Für Umweltforschung; Alemania Fil: Adler, Peter B. State University of Utah; Estados Unidos Fil: Bagchi, Sumanta. Indian Institute Of Science; India Fil: Bakker, Jonathan. University of Washington; Estados Unidos Fil: Barrio, Isabel C. Agricultural University Of Iceland; Islandia Fil: Biederman, Lori. Iowa State University; Estados Unidos Fil: Boughton, Elizabeth H. Archbold Biological Station; Estados Unidos Fil: Bugalho, Miguel N. Universidade Nova de Lisboa; Portugal Fil: Caldeira, Maria C. Universidade Nova de Lisboa; Portugal Fil: Catford, Jane A. King's College London; Reino Unido Fil: Daleo, Pedro. Universidad Nacional de Mar del Plata; Argentina. Consejo Nacional de Investigaciones ...